A Passion to Preserve Gay Men as Keepers of Culture - Fellows, Will (The University of Wisconsin Press, 2005)
From large cities to rural communities, gay men have long been impassioned pioneers as keepers of culture: rescuing and restoring decrepit buildings, revitalizing blighted neighborhoods, saving artifacts and documents of historical significance. This penchant to preserve, though widely observed, is typically ignored or dismissed as a stereotypical gay cliché, even by many gay men themselves. A Passion to Preserve explores this authentic and complex dimension of gay men's lives by profiling early and contemporary preservationists from throughout the United States. This eye-opening and provocative book illuminates neglected facets of what it means to be gay and highlights contributions to the larger culture that gays are exceptionally inclined to make.